Cover Feature: Purinergic Signaling: Impact of GPCR Structures on Rational Drug Design (ChemMedChem 21/2020). (22nd October 2020) - Salmaso, Veronica; Jacobson, Kenneth A.
Abstract : The Cover Feature depicts the poses of two ligands at their GPCR binding sites in the framework of a capsule, highlighting the impact of GPCR structures in drug design. The poses of A3 adenosine receptor agonist MRS5698 and P2Y14 receptor antagonist PPTN at their respective receptor binding sites are shown in the left and right side of the capsule, respectively. These complexes were obtained by homology modeling of the receptors, followed by molecular docking and molecular dynamics, and have facilitated further derivatization. Recent applications of structure‐based drug design to three purinergic GPCRs are featured: P2Y1 R, P2Y14 R, and A3 AR. Cover design by Veronica Salmaso. More information can be found in the Review by Veronica Salmaso and Kenneth A. Jacobson .